Performance and Risks: Islamic Indices Compared to Conventional Indices - Agouram, Jamal; Anoualigh, Jamaa; Hssain, Lhoucine Ben; Lakhnati, Ghizlane (Asian Journal of Economics and Empirical Research, 2021)
Islamic finance is very successful in the global market, and leading traditional index providers have expanded their range and are now offering a multitude of Islamic indices to facilitate the rapid development of Islamic finance, especially Sharia-compliant funds. We will evaluate and analyze both the Islamic and non-Islamic indices and their volatility, considering Islamic finance's rise in popularity. The first purpose of this research is to establish a comparison and then analyze the results of the performance of the Dow Jones World Index (DJW) and its Islamic counterparts. The analysis of the outcomes will be in terms of performance measures. On the basis of the total risk, we will then compare the Dow Jones World Index and its Islamic counterparts. This risk would usually be captured by both Value-at-Risk and Conditional Value-at-Risk. The purpose of this paper is to demonstrate whether Islamic indices are higher than the conventional index and whether the overall risk for Islamic indices is lower than for the conventional index.